HUBUNGAN PENDIDIKAN IBU DENGAN STATUS GIZI ANAK USIA 3-5 TAHUN DI DESA SINDANGSARI KECAMATAN CIKONENG KABUPATEN CIAMIS TAHUN 2019 - Ana Samiatul Milah; Ade Zaqiah (Journal of Midwifery and Public Health, 2019)
Nutrition / nutrition problems occur in every life cycle and throughout the life cycle of women, starting from the womb (fetus), infants, children, adults and old age. The period of the first two years of life is a critical period, because during this period there was very rapid growth and development. Nutritional disorders that occur in this period are permanent, cannot be recovered even though nutritional needs in the next period are met. Data obtained from the Cikoneng Health Center in Cikoneng Sub-district of Ciamis District in 2017 in January the nutritional status of children under five was obtained, but the total number of malnourished sufferers was 29 children. Then in 2018 experienced an increase of 46 children consisting of 42 undernourished children and 4 malnourished children out of 789 children who could be measured and in 2019 there were 213 people. The method used in this research is analytic descriptive research method. The population in this study were all mothers and toddlers aged 3-5 years in Sindangsari Village, Cikoneng District, Ciamis Regency amounted to 213 people. The sampling technique used was using random sampling technique. The results of this study were the results of research of 68 respondents, mother's education in the secondary education category with good nutritional status in children as many as 15 (62.5%) respondents. Hypothesis test results using chi square obtained p value of 0.014 smaller than alpha 0.05. From the results of this study it can be concluded that there is a relationship between maternal education and nutritional status of children aged 3-5 years in Sindangsari Village, Cikoneng District, Ciamis Regency with a p-value of 0.014 smaller than alpha = 0.05. The results of the study are expected to contribute scientifically to the improvement of knowledge related to child growth and development problems and can be used as information to increase knowledge about the importance of child development for the community in order to improve the health and welfare of mothers and children, can also be for children to be healthy in terms of nutritional intake, good health status from nutritional status and health assessment, one of the steps in efforts to conduct nutrition counseling to the community, especially mothers who have children under five at the age of 3-5 years.